Pliometría post lesiones músculotendinosas en miembros inferiores de futbolistas. federación deportiva de Chimborazo, 2019” - Shirley Nathaly, Robalino Aldaz (2019)
The research entitled "Plyometrics post tendinous muscle injuries in lower limbs of soccer players, in “Federación Deportiva de Chimborazo”, 2019” aimed to apply the plyometric technique as a complement to physiotherapeutic rehabilitation, with a population of 23 soccer players under 17 and a sample of 22, during the period September to October 2019. For the data collection process the methodology used was mixed with a type of exploratory, application, qualitative, quantitative, prospective, deductive, comparative and field research, where the intervention is carried out by applying the Daniel´s Test , goniometric test, postural test, pain scale, muscle mass measurement and jump test. At the end of the application it is found that the plyometric technique is effective as a complement in the physiotherapeutic treatment, because they have to do with the soccer players of the study group, who execute the extra series of plyometric exercises with an adequate dosage, present improvement at the level of muscular mass, therefore they obtained benefits in aspects of the capacity of explosive force in both horizontal and vertical jump in a 3 to 1 ratio, contributed in the execution of changes of directions, lateral sprint and resistance; avoiding recurrences in the course of the investigation time.